Association between Serum Zinc Level and Cutaneous Viral Warts: A Case Control Study - Ranjit, Annu; Rajbhandari, Sudharshan Lal; Gautam, Narayan; Poudyal, Yogesh (Nepal Journal of Dermatology, Venereology & Leprology, 2019)
Introduction: Cutaneous viral warts are one of the common skin disorders in general population which can affect any age group and any gender in any country and pose a significant health problem. A possible association with zinc has been suggested in previous studies. Zinc is known to be required for efficient functioning of immune system. Objective: To find out the association between serum zinc level and cutaneous viral warts. Materials and methods: In this case-control study, total of hundred patients were enrolled. Among them 50 (males – 27, females – 23) with cutaneous viral warts were taken as cases and 50 (males – 25, females – 25) healthy individuals were taken as controls after matching the age and sex. The patients were selected from Dermatology outpatient Department of Universal College of Medical Sciences Teaching Hospital, Bhairahawa, Nepal. The serum zinc level was measured using spectrophotometry principle. Results: The mean serum zinc level in the cases and controls were 80.50±37.24 mg/dl and 104.31±25.31 mg/dl respectively. Significant difference in serum zinc level was observed between cases and controls (p=0.0001). There was a strong association between low serum zinc level and cutaneous viral warts (OR=7.37; 95% CI=1.98 – 27.31; p=0.0028). Conclusion: Serum zinc level in patients with cutaneous viral warts was significantly low as compared to the healthy controls.